Incidence of Strokes in Brazil between 2018 and 2022 and their correlations with the COVID-19 pandemic (Research, Society and Development, 2024)
The present study provides a comprehensive analysis of the trends in Stroke (CVA) and COVID-19 in Brazil from 2018 to 2022. Using data provided by the Brazilian Ministry of Health, the incidence and mortality of these two diseases were examined in each of the five regions of Brazil and then compared with the country's population distribution. In this context, fluctuations in both the incidence and mortality of COVID-19 were observed in the Brazilian regions from 2020 to 2022. Overall, the proportions between the incidence of strokes and the population size remained stable in all regions, while the distribution of COVID-19 showed certain variations. There was an increase of more than 10% in the number of stroke hospitalizations in all five regions in 2022 compared to the initial year of the study in 2018. This trend was consistent across all regions, potentially suggesting a correlation between the increase in stroke hospitalizations and the COVID-19 pandemic. Based on this, it is suggested that further research be conducted to observe if these trends will continue over the years. The objective of the present study was to measure the variation in the incidence and deaths from stroke in Brazil from 2018 to 2022, and correlate them with the peak of the COVID-19 pandemic, analyzing if there was a correlation in the increase of cases of both diseases.